Efficient algorithms to solve a class of resource allocation problems in large wireless networks - Luo, Jun. (2009)
We focus on efficient algorithms for resource allocation problems in large wireless networks. We first investigate the link scheduling problem and identify the properties that make it possible to compute solutions efficiently. We then show that the node on-off scheduling problem shares these features and is amenable to the same type of solution method. Numerical results confirm the efficiency of our technique for large scale problems. We also extend the technique to the case where the objective function is non linear showing that our technique blends smoothly with a sequential linear programming approach. Numerical results for across layer design with a nonlinear fairness utility show that it is possible to compute optimal solutions for large wireless networks in reasonable CPU time.